Haywire : Discord in Maine's Logging Woods and the Unraveling of an Industry - Egan, Andrew (Book collections on Project MUSE., 2022)
"Logging in the northern forest has been romanticized, with images of log drives, plaid shirts, and bunkhouses in wide circulation. Increasingly dismissed as a quaint, rural pastime, logging remains one of the most dangerous jobs in the United States, with loggers occupying a precarious position amid unstable markets, expanding global competition, and growing labor discord. Examining a time of transition and decline in Maine's forest economy, Andrew Egan traces pathways for understanding the challenges that have faced Maine's logging community and, by extension, the state's forestry sector, from the postwar period through today. Seeking greater profits, logging companies turned their crews loose at midcentury, creating a workforce of independent contractors who were forced to purchase expensive equipment and compete for contracts with the mills. Drawing on his own experience with the region's forest products industry, interviews with Maine loggers, media coverage, and court documents, Egan follows the troubled recent history of the industry and its battle for survival"--